Penyusunan Laporan Keuangan Sederhana Berbasis Excel untuk Usaha Mikro - Umi Hayati; Willy Prihartono; Agung Saeful; Agung Triyono (CV. Multi Kreasi Media, 2022)
Micro businesses are the backbone of the Indonesian economy, but there are still many micro businesses that do not have the ability to keep good and systematic financial records. The main problem faced is the lack of understanding of the importance of financial statements as well as limitations in the use of complex accounting technology. This service activity aims to increase the capacity of micro business actors in preparing simple financial reports by utilizing Microsoft Excel. The program is conducted through face-to-face training, hands-on practice, and intensive mentoring. The training materials include basic introduction to accounting, making profit and loss statements, cash flow statements, and using Excel templates that have been prepared by the team. The methods used included group discussions, case studies, simulations, and evaluation of results. The results of the activities showed that the partners experienced a significant improvement in their understanding and financial recording skills. Some partners have implemented daily transaction recording and are able to prepare financial reports independently. In addition, awareness of the importance of financial management for business sustainability also increased. Future recommendations include the need for further training, development of digital-based financial recording applications, and collaboration with financial institutions to access funding. This activity proves that with the right approach, micro-entrepreneurs can be encouraged to be more professional in managing their finances, thus increasing their competitiveness and business sustainability amidst dynamic economic challenges.